The Ability of Social Services in the Centre of Makhmur District - Sasan Hikmat Ali; Mudhafar Ahmed Rasool (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Social services are one of the basic services of the city and the basic necessity of any human in his daily life And the humanitarian community is trying to provide it despite the differences in the political and economic system,Because community service is the main basis for developing and advancing the community,And the measure of progress or dispersion of each community,Also, there is a strong relationship between the measurements of social services and development measurements,In a way, the level of happiness decides on the direction of development in any part of the world’s wars,Because of this, development needs a single right to do its work The purpose of this investigation is to improve the division of public services in the centre of Makhmur district and Showing the level of their ability to the residents of the area The problem of investigating is the lack of people in the division of social services on the level of the city of Makhmur The assumption of investigating the geographical information system through classical selection, degradation, and division of social services in Makhmur district and The results are more accurate and accurate and it is easier to get their map in terms of photography The research plan is aimed at investigating the objectives that will be disbursed to four part:The first part is mentioned in the theoretical context and introducing the area of investigation, in The second part is to provide the most important public services in the district centre The third part is highlighted. Analyze service location properties The four-part focus has been focused on evaluating education and health services Because of the two levels of services at the level of public services